2018
DOI: 10.1097/ico.0000000000001480
|View full text |Cite
|
Sign up to set email alerts
|

Tripolymeric Corneal Coating Gel Versus Balanced Salt Solution Irrigation During Cataract Surgery: A Retrospective Analysis

Abstract: Purpose:To compare the protective properties and ease of manipulation during cataract surgery of corneal coating with a gel (eyeDRO; AL.CHI.MI.A. S.R.L, Italy) and corneal irrigation with balanced salt solution (BSS).Methods:We analyzed the data of 51 patients receiving either eyeDRO or BSS during routine cataract surgery performed within a 20-day period in 2016. The selected parameters were intraoperative clarity and ease of manipulation; postoperative epithelial integrity; and patient discomfort.Results:Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A previous study reported that corneal erosion occurred in 60% of the eyes with an OVD applied to the ocular surface during surgery but in 90% of control eyes at 2 hours after surgery. At postoperative 2 and 24 hours, the study group showed significantly improved foreign body sensation [17]. In previous studies, some indicators of dry eye syndrome showed improvement in a short time-period of 2 to 3 days after surgery in the group with OVD applied to the ocular surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that corneal erosion occurred in 60% of the eyes with an OVD applied to the ocular surface during surgery but in 90% of control eyes at 2 hours after surgery. At postoperative 2 and 24 hours, the study group showed significantly improved foreign body sensation [17]. In previous studies, some indicators of dry eye syndrome showed improvement in a short time-period of 2 to 3 days after surgery in the group with OVD applied to the ocular surface.…”
Section: Discussionmentioning
confidence: 99%
“…An ophthalmic viscosurgical device (OVD) used to maintain anterior chamber space and prevent damage to intraocular tissue during cataract surgery is excellent for protection of corneal endothelial cells [16]. Reports have indicated that OVD applied to the ocular surface during cataract surgery results in less ocular surface damage 2 hours and 24 hours after operation than balanced salt solution (BSS) irrigation on the surface [17]. Therefore, an OVD thinly coated on the corneal surface during cataract surgery is expected to greatly reduce corneal epithelial damage from continuous intraoperative perfusion of the ocular surface without interfering with the visual field.…”
mentioning
confidence: 99%